Lãnh đạo chuyển đổi, năng lực đổi mới và hiệu quả hoạt động của doanh nghiệp - Bùi Quang, Hùng; Trịnh Thùy, Anh; Nguyễn Ngọc, Thông (JOURNAL OF ASIAN BUSINESS AND ECONOMIC STUDIES, 2023)
This paper presents the results of research on the impact of transformational leadership on innovation capacity and firm performance. Structural equation modeling (SEM) and fuzzy set comparative analysis (fsQCA) are employed as the research methods in this paper. A sample including 212 directors and senior leaders of manufacturing and service companies from Ho Chi Minh City, Dong Nai, Binh Duong responded to the survey questionnaire. Research result shows that transformational leadership has a positive effect on a firm’s innovation capacity and firm performance. In addition, fsQCA results demonstrate that the combination of innovation competence components creates the necessary conditions for the existence of firm performance.